2002
DOI: 10.1080/14681990220149040
|View full text |Cite
|
Sign up to set email alerts
|

Health challenges for older women: Some implications for sexual health

Abstract: The case for looking beyond prejudice and myth at the sexual experiences of both men and women, and at how their experiences are connected to questions of sexual health, is becoming increasingly important as the proportion of the population over 50 continues to expand over the next 50 years. This paper summarizes the ndings of a literature review, commissioned by The Pennell Initiative For Women's Health, which looked at how sex and sexuality interacts with common health problems faced by women in the second h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…For instance, interested researchers should focus on the sexual health of nonmainstream groups, such as older women with nontraditional sexual orientations or those living with different kinds of physical limitations and disabilities. Also, little empirical evidence is published on the relationship between ethnicity and the sexual health of older women (as pointed out by Vincent [ 6 ]). Unfortunately, diversity of any kind has been neglected in the investigation of older women's sexual desire and sexual functioning in general.…”
Section: Suggestions For Doctor-older Female Patient Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, interested researchers should focus on the sexual health of nonmainstream groups, such as older women with nontraditional sexual orientations or those living with different kinds of physical limitations and disabilities. Also, little empirical evidence is published on the relationship between ethnicity and the sexual health of older women (as pointed out by Vincent [ 6 ]). Unfortunately, diversity of any kind has been neglected in the investigation of older women's sexual desire and sexual functioning in general.…”
Section: Suggestions For Doctor-older Female Patient Communicationmentioning
confidence: 99%
“…The authors' supplementary analyses revealed that the mechanism most likely linking older women's stressors and poor health to sexual issues such as low sexual desire is poor mental health, such as high levels of stress, anxiety, and depression (as discussed later in this paper). Conversely, an active sex life appears to provide many older people with a buffer against ill health in later life [ 6 ]. Because sexual activity has positive effects on older adults' physical health, it is important to resume a sexual relationship after an illness or traumatic event.…”
Section: Introductionmentioning
confidence: 99%
“…These include: (a) outliving men (in almost every country in the world; Austad 2006), which typically results in the lack of access to a partner (Pennell Initiative for Women’s Health 1998) and forces older women into sexual abstinence (Vincent 2002); (b) an emotionally distant relationship with an intimate partner (Johnson 1998); (c) misinformation, misconception, and prejudice (Butler and Lewis 1988); (d) the culturally induced belief that sexual activity is for the young (Lobsenz 1974); (e) boredom and fear of failure (Rubenstein 1978); (f) needs of family members that result in strained emotional energy within the older couple (Kingsburg 2000); (g) lack of privacy (Le Gall, Mullet, and Shafighi 2002); (h) reduced levels of oestrogen and other hormones (during and after menopause) resulting in lower levels of sexual desire (Benbow and Jagus 2002), as well as in decreased vaginal lubrication and related painful intercourse (Dennerstien 1996); (i) illness and medication use (Gefland 2000), which often disrupt women’s sexual functioning at all ages (Laganà et al 2001); (j) poor body image (Leiblum 1991); and (k) erectile dysfunction in a sexual partner (Kingsburg 2000), with over 50% of men experiencing it by age 50 at a rate increasing by nearly 10% every decade (American Psychiatric Association 2000). …”
mentioning
confidence: 99%